A multiscale-compatible approach in modeling ionic transport in the electrolyte of (Lithium ion) batteries - Salvadori, A.; Grazioli, D.; Geers, M.G.D.; Danilov, D.; Notten, P.H.L. (Journal of power sources, 2015)
A novel approach in modeling the ionic transport in the electrolyte of Li-ion batteries is here presented. Diffusion and migration processes govern the transport of ions in solution in the absence of convection. In the porous electrode theory [1] it is common to model these processes via mass balance equations and electroneutrality. A parabolic set of equations arises, in terms of a non constant electric field which is afflicted by the paradox of being generated without electrical charges. To remedy this contradiction, Maxwell's equations have been used here, coupled to Faraday's law of electrochemical charge transfer. The set of continuity equations for mass and Maxwell's equations lead to a consistent model, with distinctive energy characteristics. Numerical examples show the robustness of the approach, which is well suited for multi-scale analyses [2,3]. •We developed a novel approach in modeling ionic transport in the electrolyte.•We considered fundamental laws with no recourse to electroneutrality equation.•Constitutive theory, weak forms, simulations are framed in a rigorous PDEs setting.•Multiphysics coupling is fully 3D, 2D simulations are performed.•Microstructural and stress analysis are made possible by the present formulation.